Monochorionic monoamniotic live twin ectopic pregnancy: a rarity - Dhama, Vandana; Gupta, Sonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The incidence of unilateral live twin ectopic pregnancy is approximately 1:1,25,000 but increased in last few decades due to increased use of fertility drugs for ovulation induction, superovulation and assisted reproductive technology. It is also associated with increased incidence of pelvic inflammatory diseases. Patient was 30 years old G3P2L2 who presented to OPD of this LLRM medical college, Meerut with complain of amenorrhoea of two and half months. Pelvic examination revealed tenderness in lower abdomen, left adnexal fullness and tenderness without any bleeding. On USG, left adnexal monochorionic monoamniotic ectopic twins with normal cardiac activity. Exploratory laparotomy followed by left sided salpingectomy was done and patient was discharged with satisfactory condition. This is a very rare case and PID is also among risk factors and may also cause twin ectopic pregnancy.